THE EFFECT OF THE TOKEN ECONOMY METHOD ON REDUCING ONLINE GAME ADDICTION BEHAVIOR IN JUNIOR HIGH SCHOOL STUDENT: SINGLE SUBJECT RESEARCH - Mahmudah, Siti; Affandi, Ghozali Rusyid (International Journal Multidisciplinary (IJMI), 2025)
Objective: Therefore, the purpose of this study aims to determine the effect of token economy techniques to reduce the duration of gaming behavior in adolescents. Method: The method used is quantitative quasi single subject experiment with single subject research design. This study uses ABA methods and instruments using duration recording. the research subject is a 13-year-old male adolescent who shows addictive behavior playing online games, lack of interest in socializing. The data collection technique uses purposive sampling and data analysis using analysis in conditions and analysis between conditions. The token economy technique is applied by giving stickers when adolescents reduce the duration of playing according to the conditions and collected to be exchanged for prizes. Results: The results showed that this method succeeded in reducing adolescents' gaming duration from 6-12 hours to 2-3 hours after treatment. Novelty: This study applies a token economy technique using a sticker-reward system to reduce gaming duration in adolescents within an ABA single-subject design, targeting not only gaming behavior but also underlying social disengagement patterns—an approach not widely implemented in prior similar behavioral interventions.